2020
DOI: 10.1055/s-0040-1715084
|View full text |Cite
|
Sign up to set email alerts
|

A New Technique to Puncture and Remove a PTCA Balloon that Fails to Deflate

Abstract: We present the first clinical report and describe the technique of using a modified Heartrail II guiding catheter to successfully puncture and remove a coronary angioplasty balloon that failed to deflate after stent implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…13)24)26) The EuroPCR group has proposed a number of rescue therapeutic options in cases of non-deflatable coronary balloons (www.pcronline.com). 19) Brinjikji et al reported groin complications (groin or retroperitoneal hematoma, femoral artery bleeding, etc.) caused by large groin sheaths, 6) whereas catheter instability, carotid artery dissection, and difficult aortic arch have been identified as potential complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13)24)26) The EuroPCR group has proposed a number of rescue therapeutic options in cases of non-deflatable coronary balloons (www.pcronline.com). 19) Brinjikji et al reported groin complications (groin or retroperitoneal hematoma, femoral artery bleeding, etc.) caused by large groin sheaths, 6) whereas catheter instability, carotid artery dissection, and difficult aortic arch have been identified as potential complications.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are various complications associated with endovascular procedures, there have been reports of coronary artery intervention for complications related to deflation failure [ 13 , 24 , 26 ]. The EuroPCR group has proposed a number of rescue therapeutic options in cases of non-deflatable coronary balloons ( www.pcronline.com ) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%